Investigating the use of torrefied biochar in agriculture for carbon sequestration - Tutton, Charlotte Eliza (2024)
Multiple different approaches are needed globally to mitigate the effects of climate change and reach carbon reduction targets. The Royal Society and Royal Academy of Engineering integrated assessment models indicate that Greenhouse Gas (GHG) removal by 2100 must equate to 230 giga tonnes of carbon, which corresponds to around a 0.4oC temperature reduction. The UK has set a target to be net (carbon) zero by 2050 which means substantial changes to industries must take place, in addition to utilising a range of GHG removal technologies. A key mechanism for capturing and storing CO2, is a process known as carbon sequestration. The key challenge for this is cost of capture, but biochar production is one method of carbon sequestration that has the potential to be economically viable due to the wide range of applications for the carbon-rich, stable material.